Gastrectomy with or without omentectomy for cT3–4 gastric cancer: a multicentre cohort study. Issue 12 (20th May 2020) - Ri, M; Nunobe, S; Honda, M; Akimoto, E; Kinoshita, T; Hori, S; Aizawa, M; Yabusaki, H; Isobe, Y; Kawakubo, H; Abe, T
Abstract: Background: Omentectomy is performed widely for locally advanced gastric cancer to prevent disease recurrence. However, its clinical benefit is unknown. Methods: This retrospective cohort study compared the outcome of gastrectomy with preservation of the omentum (GPO) and gastrectomy with resection of the omentum (GRO) among patients with cT3–T4 gastric cancer who underwent gastrectomy between 2006 and 2012 in one of five participating institutions. A consensus conference identified 28 variables potentially associated with outcome after gastrectomy for the estimation of propensity scores, and propensity score matching (PSM) was undertaken to control for possible confounders. Postoperative surgical outcomes, overall survival and disease recurrence were compared between GPO and GRO. Results: A total of 1758 patients were identified, of whom 526 remained after PSM, 263 in each group. Median follow-up was 4·9 (i.q.r. 3·1–5·9) years in the GRO group and 5·0 (2·5–6·8) years in the GPO group. The incidence of postoperative complications of Clavien–Dindo grade III or more was significantly higher in the GRO group (17·5 versus 10·3 per cent; P = 0·016). Five-year overall survival rates were 77·1 per cent in the GRO group and 79·4 per cent in the GPO group ( P = 0·749). There were no significant differences in recurrence rate or pattern of recurrence between the groups. Conclusion: Overall survival and disease recurrence were comparable in patients with cT3–4 gastric cancer who underwent GPO or GRO. Graphical Abstract: This study investigated whether omentum-preserving gastrectomy for locally advanced gastric cancer is non-inferior to omentum-sparing gastrectomy, with rigorous adjustment for all known potential confounding factors associated with outcomes. Five-year overall survival rates were 79·4 and 77·1 per cent respectively. Oncologically, omentum-preserving and omentum-resecting gastrectomy yielded similar outcomes. No difference